Safety and Efficacy of Empagliflozin and Diuretic Use in Patients with Heart Failure and Preserved Ejection Fraction: A Post Hoc Analysis of the EMPEROR-Preserved Trial - Butler, Javed; Usman, Muhammad Shariq; Filippatos, Gerasimos; Ferreira, João Pedro; Böhm, Michael; Brückmann, Martina; Januzzi, James L.; Kaul, Sanjay; Piña, Ileana L.; Ponikowski, Piotr; Senni, Michele; Sumin, Mikhail; et al. (JAMA cardiology, 2023)
The diuretic effect of sodium-glucose cotransporter 2 inhibitors may result in interaction with background diuretic therapy in patients with heart failure and preserved ejection fraction (HFpEF).To assess the safety and efficacy of empagliflozin in combination with background diuretic therapy and the association of empagliflozin with the need for conventional diuretics.This was a post hoc analysis of the Empagliflozin Outcome Trial in Patients with Chronic Heart Failure with Preserved Ejection Fraction (EMPEROR-Preserved). EMPEROR-Preserved was a phase 3, randomized, placebo-controlled, double-blind clinical trial conducted from March 2017 to April 2021. Patients with class II to IV heart failure and left ventricular ejection fraction greater than 40% were included. Of 5988 patients enrolled, 5815 (97.1%) had baseline data on diuretic use and were included in this analysis, which was conducted from November 2021 to August 2022.Participants in EMPEROR-Preserved were randomized to empagliflozin or placebo. In this analysis, participants were divided into 4 subgroups: no diuretics and furosemide-equivalent diuretic dose of less than 40 mg, 40 mg, and greater than 40 mg at baseline.The main outcomes of interest were first hospitalization for heart failure (HHF) or cardiovascular death (CV death) and its components. Association of empagliflozin vs placebo with outcomes by baseline diuretic status (no diuretic vs any dose) and dose (no diuretic, <40 mg, 40 mg, and > 40mg) was assessed. Association of empagliflozin use with changes in diuretic therapy was also studied.Among 5815 patients (mean [SD] age, 71.9 [9.4] years; 2594 [44.6%] female) with known baseline diuretic use, 1179 (20.3%) were not taking diuretics, 1725 (29.7%) were taking less than 40 mg, 1772 (30.5%) were taking 40 mg, and 1139 (19.6%) were taking greater than 40 mg. In the placebo arm, patients with higher diuretic doses had worse outcomes. Empagliflozin decreased the risk of HHF or CV death, regardless of background diuretic status (hazard ratio [HR], 0.81; 95% CI, 0.70-0.93] for the diuretic group vs HR, 0.72; 95% CI, 0.48-1.06 for the nondiuretic group; P for interaction = .58). Similarly, diuretic status was not associated with changes in improvements in first HHF, total HHF, rate of decline in estimated glomerular filtration rate, and Kansas City Cardiomyopathy Questionnaire 23 clinical summary score with empagliflozin. Findings were consistent when patients were categorized by diuretic dose. Empagliflozin was associated with a decreased likelihood of diuretic dose escalation (HR, 0.74; 95% CI, 0.65-0.84) and an increased likelihood of de-escalation (HR, 1.15; 95% CI, 1.02-1.30). Empagliflozin was associated with an increased risk of volume depletion in patients taking diuretics (HR, 1.34; 95% CI, 1.13-1.59).In this study, treatment with empagliflozin was similar regardless of diuretic use or dose. Empagliflozin use was associated with decreased conventional diuretic dosing.ClinicalTrials.gov Identifier: NCT03057951